THE RELATIONSHIP BETWEEN LEARNING STYLE PREFERENCES AND INTEREST IN YOUTUBE FOR LEARNING ENGLISH AT UNIVERSITAS RIAU KEPULAUAN - Chairiah, Annisa Melfida; Ramadhani, Nursyahidah Suci; Aqilla, Dhiya Veeza; Aguspriawan, Muryadi; Navisa, Sayyida; Syahrila, Farah Dieba Nashwa; Dewi, Desi Surlitasari; Ratnasari, Sri Langgeng; Ciptono, Ciptono; Niko, Triyanda Desma (JURNAL DIMENSI, 2024)
Advances in digital technology in the 21st century have changed the way students access and interact with learning materials, particularly through platforms like YouTube. This study aims to examine the relationship between students' learning style preferences—based on the VARK (Visual, Aural, Read/Write, Kinesthetic) model—and their interest in using YouTube as an English language learning medium. The research design employed a quantitative correlational approach applied to a sample of 20 sixth-semester students from the University of Kepulauan Riau. Data were collected using the VARK questionnaire and a Likert scale instrument adapted from validated research to measure interest in YouTube-assisted English language learning. The results of the normality test indicated that the data for the variables of interest were normally distributed (p = 0.148). However, due to the categorical nature of the learning style variables, Spearman's Rank Correlation was used. The findings revealed a weak and insignificant negative correlation (ρ = -0.266, p > 0.05) between learning style preferences and students' interest in YouTube-based English language learning. This suggests that YouTube, as a multimodal learning platform, can attract a diverse range of learners, regardless of their preferred learning styles. This study recommends integrating YouTube into teaching practices and conducting further research with broader variables and larger samples.